2018
DOI: 10.25186/cs.v13i3.1458
|View full text |Cite
|
Sign up to set email alerts
|

NITROGEN FERTILIZERS AND OCCURRENCE OF Leucoptera coffeella (Guérin-Mèneville & Perrottet) IN TRANSPLANTED COFFEE SEEDLINGS

Abstract: The coffee leaf-miner (CLM) Leucoptera coffeella (Lepidoptera: Lyonetiidae) is one of the main pests of coffee plants in Brazil. Its occurrence in the crop is directly related to the physiological state and growth characteristics of coffee plants, in turn related to plant nutrition. The present work, therefore, aimed to evaluate the effect of nitrogen sources on the occurrence of CLM in coffee seedlings. The fertilizers used were ammonium sulfate, urea, and organomineral. The number of leaves mined by CLM and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…Also, Agathokleous et al (2019) have revealed the bio-inhibitory impacts of AS for insects on brassica plants even under ozone pollution. But this effect may be altered under excessive or high AS doses, especially for insect defense (Sabino et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Also, Agathokleous et al (2019) have revealed the bio-inhibitory impacts of AS for insects on brassica plants even under ozone pollution. But this effect may be altered under excessive or high AS doses, especially for insect defense (Sabino et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Eventually, without adequate cultural treatments, the infestation can lead to the death of the plant. A relationship between the feeding damage of CLM and the application of synthetic fertilizers has been described in the literature [41,42]. The amount of free amino acids and reducing sugars in the metabolic system of coffee plants is related to nutritional imbalance and susceptibility to pests.…”
Section: Larval Feeding Behaviormentioning
confidence: 99%
“…The amount of free amino acids and reducing sugars in the metabolic system of coffee plants is related to nutritional imbalance and susceptibility to pests. Plants fertilized with organic material showed a decrease of up to 50% of leaf mines [41].…”
Section: Larval Feeding Behaviormentioning
confidence: 99%
“…A relationship between the feeding damage of CLM and the application of synthetic fertilizers has been described in the literature [28,29]. The amount of free amino acids and reducing sugars in the metabolic system of coffee plants is related to nutritional imbalance and susceptibility to pests.…”
Section: 2larval Feeding Behaviormentioning
confidence: 99%
“…The amount of free amino acids and reducing sugars in the metabolic system of coffee plants is related to nutritional imbalance and susceptibility to pests. Plants fertilized with organic material showed a decrease of up to 50% of leaf mines [28].…”
Section: 2larval Feeding Behaviormentioning
confidence: 99%